العلاقات التركيبية و الدلالية في الجملة الشرطية - رؤية لسانية - - فضل, عاطف; كتانة, حسين (Revues faculté des lettres et des langues; No 12 (2013): مجلة كلية الآداب واللغات, 2014)
يرمي البحث إلى تقديم صورة واضحة عن الجملة الشرطية لدى النحاة العرب، وفق منهج لغوي حديث يقوم على التحليل اللغوي الوصفي المستمد من واقع اللغة، وليس من فكرة الإسناد، أو سيطرة العامل على الجملة، وذلك أن الجملة عنصر مرن تقبل بمرونتها أداء المعنى الذي نطقت العرب الجملة لأجله.         وللوصول إلى هذا المعنى لا بدّ من استثناء ما لا علاقة له بصلب التوصيف اللغوي الخالص، كالعلل، والأقيسة، والافتراضات العقلية الجدلية، وغير ذلك من استطرادات النحويين التي أثقلت الدرس النحوي بشكل عام، وخرجت بالجملة الشرطية عن مسارها التركيبي والدلالي بشكل خاص.   The research targets to present a clear idea about the conditional clause according to Arab Grammarians based on Linguistic curriculum depending on descriptive linguistic analysis derived from real language, and not based on the idea of the reference or the domination of the factor on the sentence, that is, as a sentence is a flexible element which through its flexibility accepts expressing the meaning for which the Arabs uttered the sentence.                   For conveying this meaning, we should exclude every thing that has nothing to do with the core of pure linguistic description such as : causes and conversational mental assumptions as well as the grammarian's overexpansion that overloaded the syntax lesson in general and helped the deviation of the conditional clause from its structural and symantic route in particular.